Influencer Credibility and Consumer Usage Decisions in the Imported Skincare Market: Evidence from TikTok Users in Depok, Indonesia - Dinda Lutfiyanti Achmad; Veranus Sidharta (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines the influence of influencer credibility on consumer usage decisions in the imported skincare market, focusing on TikTok users in Depok, Indonesia. The rapid growth of short-video platforms has changed how young consumers search for beauty information, evaluate product quality, and decide to use skincare products. TikTok influencers are increasingly viewed as persuasive digital sources because they combine visual demonstrations, personal experience, and interactive communication. This research employed a quantitative explanatory survey involving 168 university students who had viewed imported skincare recommendations from the TikTok account @tasyafarasya. Data were collected through a structured Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares with SmartPLS 4. The findings show that influencer credibility has a positive and significant effect on consumer usage decisions, with a path coefficient of 0.717, a T-statistic of 8.790, a P-value of 0.000, and an R-square of 0.514. These results indicate that credibility explains 51.4% of the variance in students' decisions to use imported skincare products. The study contributes to digital marketing and consumer behavior literature by highlighting the role of credible beauty influencers in shaping skincare consumption decisions within contemporary social commerce and influencer marketing practices contexts.